Veterinarians - Ready, Dee. (Mankato, MN : Bridgestone Books, 1997)
Explains the clothing, tools, schooling, and work of veterinarians.
Includes bibliographical references (p. ) and index.
Keywords: Veterinarians -- Juvenile literature; Veterinary medicine -- Vocational guidance -- Juvenile literature; Veterinarians; Veterinary medicine; Occupations